The results of american thought - Campbell, Charles Albert (My University, 1891)
Introduction: Human history is a record of oppositions and transformations. From time so remote that scholastic inquiry wearies in calculation, man has found in his fellow, an enemy or a deliberate antagonist. Distrustful, incredulous and relentless, humanity often seems wholly devoid of a single conscientious principle. An inherent conquering passion for exaltation seems to pervade its entire being, and he who dares contradict it, does so at his peril. Not alone for wealth, has this ambitious struggle been made invading the sacred domain of religious brotherhood, it has marred the beauty and spotless purity of divinity established evade England, with threatening and emerging stone to rivet upon her subjects the powerful chains of a state religion – made a forced confession, the purgation of citizenship.
Citation: Campbell, Charles Albert. The results of american thought. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Government; Politics; England; Revolution; Theses; Manuscripts (documents)